Evaluation of Various Digital Controllers for Forward Converter with Active Clamp - Ravindra Janga; Sushama Malaji (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This research paper presents the design issues of digital Controllers for Forward Converter with Active Clamp circuit (ACFC). Brief review of Working Principle and mathematical modelling of the converter is first given. The importance of Digital Controllers for forward converter and design procedure is described in detail. And the validity of designed controllers and achievement of desired compensation is verified by the results of implemented digital controllers to Active clamp forward Converter (ACFC). Finallly results are analyzed by applying disturbances at both supply end and Load ends of the converter. And the conclusions are made based on obtained results of Voltage Mode Controller (VMC) by comparing with the results of the Current Mode Controller (CMC).